Hubungan antara Psyhological Well Being dan Work Engagement pada Pekerja Kontruksi Lapangan PT Bumi Pali - Tamarani, Agnesia Tamarani; Almigo, Nuzsep (Program Studi Bimbingan dan Konseling FKIP Universitas Islam Jember, 2024)
This research aims to determine the relationship between psychological well-being and work engagement in field construction workers at PT Bumi Nusantara Indah, PALI Regency. The hypothesis proposed in this research is that there is a relationship between psychological well-being and work engagement in field construction workers at PT Bumi Nusantara Indah, PALI Regency. The population in the study was 150 field construction workers with a sample size of 105 field construction workers obtained through a random purposive sampling technique. The measuring instruments used are the psychological well-being scale and the work engagement scale. The data analysis technique uses simple regression analysis techniques. Based on the results of the research carried out, the correlation value between the psychological well-being variable and work engagement was obtained, namely with a value of R = 0.831 with a value of R Square = 0.691 and P = 0.000 where the value of p < 0.01. This shows that there is a significant relationship between psychological well-being and work engagement of PT Bumi Nusantara Indah field construction workers.